Primary sedimentation unit design at the glycerin production wastewater treatment plant at PT X - Erna Styani (President University, 2022)
PT X has needs Waste Water Treatment Plant (WWTP) to reduce the high value of TSS and organic matter levels for the wastewater of glycerin production. The objective of the experiment is to design the dimensions of the primary sedimentation unit at PT X. This design is expected to reduce wastewater TSS levels up to 50 to 70 percent and BOD levels up to 25 to 40 percent. The design stages in this experiment include determining the quantity of wastewater discharged by PT X per day through production operations, quality testing wastewater, and designing primary sedimentation units. PT X wastewater quality testing includes measuring pH, ammonia, TSS, COD, BOD, oil & grease. The parameters are determined based on the basic oleochemical industry quality standard according to the Ministerial Regulation Environment Number 5 of 2014. The primary sedimentation unit design in WWTP PT X was rectangular. The quantity of discharge of wastewater entering primary sedimentation tank of 0.00139 m3/second and detention time designed for 4 hours. Sedimentation tank volume is based on the calculation of 10 m3 with a multiplier of 1.1 so that the actual volume of the sedimentation tank is 11 m3. Based on the calculation results, the length of the tub is 4 m, the width of the tank is 1.1 m, 2.5 m deep, and 0.5 m freeboard. TSS level allowance and BOD that occurs in the primary sedimentation unit is the TSS level of 62.99% and BOD levels of 40.82%.